A distributed CoRE-Based resource synchronization mechanism - Mazayev, A. (2021)
Representational state transfer (REST) application programming interfaces and event processing are the cornerstone of the dynamic Internet of Things. While the former is required for device interoperability, the latter is important for autonomous and responsive systems. In recent years, both topics have received a lot of attention and have been drastically changing due to the emergence of new applications, which end up working inefficiently with current standards and architectures. More recently, event processing started to move down from the top (cloud) to bottom (edge devices). At the same time, the Internet Engineering Task Force, which normally solves low-layer protocol-related problems, has also started looking at event processing and resource synchronization from a bottom-up perspective. This article explores the intersection of these efforts by making an in-depth overview of currently existing standards, and Internet drafts, that allow building complex event processing chains. Next, a new reusable and scalable event processing mechanism, which can be distributed across multiple end-devices, is introduced. Its optimal distribution across end-devices is mathematically addressed, and results confirm its effectiveness.